THE TREND AND PROFILE OF THE THORACIC SPINE SURGERY IN NEUROSURGERY DEPARTMENT FACULTY OF MEDICINE UNIVERSITAS INDONESIA – RSUP NASIONAL DR. CIPTO MANGUNKUSUMO 2012 – 2016 - Muhammad Saekhu; Bismo Nugroho; Samsul Ashari; Renindra A Aman; Hanif G Tobing; Setyowidi Nugroho (Neurologico Spinale Medico Chirurgico, 2018)
Background: Spinal surgery, in general, is increasing in number. The most frequent pathology is degenerative disease, and the most common segment is cervical and lumbar. However, there is limited information concerning the thoracic spine surgeries.Objective: The aim of this study is to describe the trend and profle of the thoracic spine (T-spine) surgeries in the Department of Neurosurgery Faculty of Medicine Universitas Indonesia – RSUP Dr.Cipto Mangunkusumo from 2012 to 2016.Method: This is a retrospective study including all patients who were undergoing T-spine surgery during the period of study from January 2012 to December 2016. The number of T-spine procedureswas recorded and plotted in the trend graph. The data consisting age, gender, indication and procedure of T-spine surgery, and duration of hospital stay were recorded from medical records.Result: In the last fve years, there was an increasing trend of T-spine surgery. A total of 68 surgeries for T-spine performed with 35 female and 33 male subjects. Majority of subjects were aged 41 to 50 years old (28%), with an indication of surgery due to tumours (68%). As many as 76% T-spine surgery was carried out non-instrumented. Duration of hospital stay was 9-13 days.Conclusion: Productive age is the most common age undergoing T-spine surgeries. A spinal tumour is the most frequent indication of the T-spine surgeries